The pleiotropic effects of micronized fenofibrate in obese menopausal women with atherogenic dyslipidemia - Franiak-Pietryga, Ida; Balcerak, Magdalena; Sikora, Joanna; Duchnowicz, Piotr; Koter-Michalak, Maria; Broncel, Marlena (Menopause Review/Przegląd Menopauzalny, 2009)
The aim of the study was to estimate the effect of micronised fenofibrate (267 mg/d) on serum lipids, fibrinogen, uric acid, glucose, C-reactive protein (hs-CRP) and erythrocyte structure membrane (membrane cholesterol, the activity of Na+/K+-ATPase) in menopausal women with metabolic syndrome (MS). Material and methods: The study comprised 20 menopausal women (mean age 56 ±4.29 years). Control group consisted of 18 healthy women (mean age 55 ±3.88 years). Before and after 4 and 12 weeks of treatment the following parameters were determined: serum lipids (total cholesterol – TC, cholesterol LDL – LDL-C, cholesterol HDL – HDL-C, TG – by enzymatic method), hs-CRP (immunoenzymatic method), fibrinogen (method of Clauss), uric acid, membrane cholesterol in erythrocytes (method of Ilcy) and Na+/K+-ATPase activity (method of Bartosz et al.). Results: It was noticed significantly higher concentrations of TC, LDL-C, TG, fibrinogen, uric acid, hs-CRP and membrane cholesterol in erythrocytes of menopausal women with MS. Fenofibrate caused a significant decrease, after 4 weeks therapy, in serum TC, LDL-C, TG, fibrinogen, uric acid and membrane cholesterol in comparison to the initial values before active therapy. The activity of Na+/K+-ATPase and hs-CRP has not significantly changed after 12 weeks of therapy. The mean values of TC, fibrinogen and uric acid after 12 weeks of therapy were similar to the control group. Conclusions: Twelve-week treatment of micronised fenofibrate was not enough efficient to compensate disorders in erythrocyte membrane structure of menopausal women with MS.